The c-Jun/RHOB/AKT pathway confers resistance of BRAF-mutant melanoma cells to MAPK inhibitors - Delmas, Audrey (Oncotarget, 2015)
The response of BRAF-mutant melanoma patients to BRAF inhibitors is dramatically impaired by secondary resistances and rapid relapse. So far, the molecular mechanisms driving these resistances are not completely understood. Here, we show that, in BRAF-mutant melanoma cells, inhibition of BRAF or its target MEK induces RHOB expression by a mechanism that depends on the transcription factor c-Jun. In those cells, RHOB deficiency causes hypersensitivity to BRAF and MEK inhibitors-induced apoptosis. Supporting these results, loss of RHOB expression in metastatic melanoma tissues is associated with an increased progression-free survival of BRAF-mutant patients treated with vemurafenib. Following BRAF inhibition, RHOB activates AKT whose inhibition causes hypersensitivity of BRAF-mutant melanoma cells to BRAF inhibitors. In mice, AKT inhibition synergizes with vemurafenib to block tumor growth of BRAF-mutant metastatic melanoma. Our findings reveal that BRAF inhibition activates a c-Jun/RHOB/AKT pathway that promotes tumor cell survival and further support a role of this pathway in the resistance of melanoma to vemurafenib. Our data also highlight the importance of using RHOB tumor levels as a biomarker to predict vemurafenib patient's response and to select those that would benefit of the combination with AKT inhibitors.